Development of a Space Rental Website Using Design Thinking - Cantika Nur Previana; Risqy Siwi Pradini; Jenike Gracelya Noke (Journal of Enhanced Studies in Informatics and Computer Applications, 2024)
The large number of events held in Malang City has created a need for a place to hold these events. This need opens opportunities for developing venue rental applications to make it easier to search and book rooms according to the needs of each event. This research develops "Paketempat", which is a rental website located in Malang City using the Design Thinking method. The DT phases used include inspiration, ideation, and implementation. The Paketempat website was successfully developed using Laravel and MySQL. Based on the TAM questionnaire distributed to 20 testers, the majority answered strongly agree or gave 3 points. This proves that Paketempat can bridge space providers and tenants easily and quickly. Through Paketempat, individuals, communities, organizations, and groups can rent a suitable venue for their desired event or activity according to their budget and needs.